Employee Performance Management At The Directorate Of Rivers And Beaches In Directorate General Of Water Resources Ministry Of Public Works And Public Housing - Singgih, Rahadi Pratomo (Lembaga Penerbitan Universitas Esa Unggul, 2021)
This examines to analyze the employee performance management in the Directorate of Rivers and Coastal at the Directorate General of Water Resources, Ministry of Public Works and Public Housing. The problem that Directorate of River and Coastal at Directorate General of Water Resources Ministry of Public Works and Housing facing are : The decrease of human resource, the decrease of effectiveness the position, the effective job, thereâ€™s Gap between director and employee, this research has made to analyze and to get description about how is Employee Performance to the Performance Management in the Directorate of River and Coastal at Directorate General of Water Resources Ministry of Public Works and Housing. The research method that used is qualitative and descriptive. While using interview and observe technique. The population in this research is employee that amount 54 people by informant 5 people. Even though the file analyses has done as qualitative and before has done observe participate where researcher combine with has checked it and researcher also action as observer. The result of this research concluded that the employeeâ€™s performance was good. The result obtained from the average value of Employee Performance Target (SKP) amounted to 90,97. Hopefully the results of this research can be useful and can improve employee performance, especially in the Directorate of River and Coastal at Directorate General of Water Resources Ministry of Public Works and HousingÂ